(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Invasive malignant melanoma is one of the most aggressive neoplasms, being responsible for 90% of skin cancer deaths; its incidence has been increasing during the last decades worldwide. The progression of the disease can occur in the form of local recurrence, lymphatic spread to regional lymph nodes, or by hematogenous metastasis to distant sites: skin, organs and bone among others. Regional and distant metastases are present in approximately 10% of patients with melanoma at the time of diagnosis, leading to a worse prognosis. Survival at 5 and 10 years in patients with distant metastases is 12%-15% and 8%, respectively. The case is presented of a patient who had a nail lesion treated for several years by a podiatrist, the lesion was worsening, thus reaching an oncological hospital, where she received adequate treatment and had total remission, continuing in medical controls.